Alternatywne źródła dochodów na obszarach wiejskich - Gniot, Aleksandra (Alternative Income Sources in Rural Areas, 2005)
This article presents current situation and future prospects of Polish rural areas. It exposes the wide disparity between the incomes per capita of Polish individuals who live in cities and those who live in rural regions. The relation between poor economic development and low quality of life in the countryside is clear. This matter creates further problems such as poor business conditions, bad infrastructure, lack of entrepreneurs, unemployment and the low level of educational attainment among the rural population. In this situation, the best solution is to create alternative income sources in agricultural regions.This paper contains an analysis of Polish entrepreneurship. Number of business start- ups keeps a growing tendency especially among small farmstead households (up to 3 ha) in the countryside.This publication indicates that demand for alternative farming products and organic products has grown over recent years, but the average market share is still low. An assessment of the potential for alternative income generation shows that there is a chance to overcome the critical situation in the countryside. Some examples of alternative income sources have been given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 242-248